2021
DOI: 10.1038/s41598-021-87079-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of lipase producer Aspergillus niger in nuts and anti-biofilm efficacy of its crude lipase against some human pathogenic bacteria

Abstract: Nuts are the natural source of healthy lipids, proteins, and omega-3. They are susceptible to fungal and mycotoxins contamination because of their high nutritional value. Twenty-five species comprising 12 genera were isolated from 80 samples of dried fruits and nuts using the dilution plate method. Peanut recorded the highest level of contamination followed by coconut; almond and raisin were the lowest. Aspergillus was the most prevalent genus and A.niger, was the most dominant species. The morphological ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Aspergillus is recognized as the most common genera causing nuts spoilage, and their ingestion may cause mycoses, especially in immunocompromised patients ( Yassein et al, 2021 ). In fact, despite the industrial importance of both Aspergillus nige r and Aspergillus ochraceus , they are recognized as producers of mycotoxins, namely ochratoxin A (OTA) and fumonisin B2 (FB2) ( Frisvad et al, 2004 , 2007 ; Dasan et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Aspergillus is recognized as the most common genera causing nuts spoilage, and their ingestion may cause mycoses, especially in immunocompromised patients ( Yassein et al, 2021 ). In fact, despite the industrial importance of both Aspergillus nige r and Aspergillus ochraceus , they are recognized as producers of mycotoxins, namely ochratoxin A (OTA) and fumonisin B2 (FB2) ( Frisvad et al, 2004 , 2007 ; Dasan et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…PUMB02 and a marine sponge-derived lipase (Lpc53E1) showed 90%-95% disruption of biofilms of various pathogens such as B. cereus, Listeria sp., E. coli, Serratia sp., and Vibrio parahaemolyticus (Kiran et al, 2014). Similarly, Yassein et al (2021) demonstrated that a lipase isolated from Aspergillus niger MW029470 achieved a 77.1%, 74.9%, 93.6%, and 95.3% inhibition of the biofilms against biofilms of Proteus mirabilis, P. aeruginosa, methicillin-resistant S. aureus, and E. coli, respectively.…”
Section: Lipase Activity Against Biofilmsmentioning
confidence: 87%
“…Similarly, Yassein et al. (2021) demonstrated that a lipase isolated from Aspergillus niger MW029470 achieved a 77.1%, 74.9%, 93.6%, and 95.3% inhibition of the biofilms against biofilms of Proteus mirabilis , P. aeruginosa , methicillin‐resistant S. aureus , and E. coli , respectively.…”
Section: Enzymes As Biofilm Removal Agentsmentioning
confidence: 87%
“…For 30 seconds, slides were stained negatively with 0.2 percent uranyl acetate. GOEL-JEM-1200 EX II electron microscope was used to investigate these slides 22 .…”
Section: Scanning Electron Microscopymentioning
confidence: 99%